The Effect of E-Service Quality dan E-Trust on Behavioral Intention (A Survey of E-Wallet Users in Indonesia Who Are Members of E-Wallet Community on Facebook) - Padilah, Nisa; Wibowo, Lili Adi; Lisnawati, Lisnawati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2025)
This study aims to obtain a description and influence of e-service quality and e-trust on behavioral intention in e-wallet users who are members of the e-wallet community on Facebook. This research is a type of descriptive and verification research with a quantitative approach. The method used in this study is the simple random sampling method with a sample size of 200 respondents. The data is processed statistically using the Structural Equation Modeling (SEM) method using the AMOS for Windows program. The results of this study found that the description of e-service quality, e-trust, and behavioral intention are in the high category. E-service quality and e-trust have a positive and significant influence on behavioral intention. This finding shows that the implementation of e-service quality and e-trust carried out by e-wallet companies will encourage behavioral intention in e-wallet users who are members of the e-wallet community on Facebook